Economic, Cultural and Educational Globalization: Perspectives of Teachers in the Classroom Music Education - Bernabé Villodre, María del Mar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2014)
The subject of Music in Elementary Education has seen big changes, because the regional structure and the migration process, which showed the shortcomings of the education system to address diversity. This article reflects on the influences of the globalization process in the educational practices of music teachers Primary and shows how they need to be trained to meet this cultural diversity. The analysis aims to show how multicultural interventions framed in intercultural denominations, which are due to poor training and terminological rules on multicultural educational contexts are developed. Summarizing, in Spain, intercultural music education has the potential to become a common and convenient practice, just that teachers be trained in accordance with its principles from the universities.